EXPERIENCE WITH COMBINATION THERAPY WITH AMELOTEX®AND COMPLIGAM B®IN PATIENTS WITH MANIFESTATIONS OF SYNOVITIS IN THE PRESENCE OF KNEE OSTEOARTHROSI - O N Bakhareva; A V Solovyeva; Lesya Vasilyevna Chichanovskaya; V M Bryantseva (Современная ревматология)
Objective: to study the efficiency of combination therapy with Amelotex®and Compligam B®in patients with osteoarthrosis with the signs of knee joint synovitis. Subjects and methods. The efficiency of combination therapy with Amelotex®and Compligam B®was studied in 40 patients. During a Phase I trial, Amelotex®was administered in a dose of 1,5 ml (15 mg) as periarticular blocks, by alternating intramuscular Compligam B®in a dose of 2,0 ml. In a Phase II trial, the intramuscular injection of these drugs was alternated. Electroneuromyography (ENMG) was performed and the levels of proinflammatory cytokine interleukin-1β (IL-1β) and IL-8 were determined over time (before and on 10 and 20 days of therapy). Quality of life was assessed by a 100-mm visual analog scale before and after therapy. Results. The early sign of therapeutic efficiency was a significant reduction in the magnitude of knee joint pain, which was observed just after completion of the Phase I trial. Diminished limb cacesthesia and crepitation were most important after the end of Phase II. Synovitis cases significantly reduced in number. Recovered peripheral nerve function was objectively supported by an increase in ENMG parameters, such as the amplitude of M responses in the peroneal nerve and sensor fiber action potential in the sural nerve. After termination of the therapy, IL-1β levels became significantly lower. Quality of life improved, as shown by VAS scores. Conclusion. The findings suggest that combination therapy with Amelotex® and Compligam B® shows clinical effectivene